Albanian households behavior towards the investment alternatives - Brikena Leka; Gentiana Sharku (Contemporary Economics, 2009)
The article presents issues related to the investment alternatives for the households and the opportunities offers especially to Albanian families by the financial market. The main part of this study consists in developing empirical models, which can explain the behavior of Albanian individuals to invest in a particular portfolio. A survey was conducted consisting in 300 questionnaires. The research covered different cities in Albania, selected basically on their size and geographical location. The models are developed the Binar Models (models with discrete values), where the dependable variables are binary. Undependable variables are category. In the developed equations are reflected the main factors influencing the probability of undertaking by individuals investments with no risk or with risk.
Keywords: 330